2019
DOI: 10.35339/ic.6.1.5-11
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Metabolism in Patients With Juvenile Idiopathic Arthritis: 10-Year Follow-Up Study

Abstract: CONNECTIVE TISSUE METABOLISM IN PATIENTS WITH JUVENILE IDIOPATHIC ARTHRITIS: 10-YEAR FOLLOW-UP STUDYShevchenko N.S., Panko N.O., Rakovska L.O., Holovko T.O. Connective tissue remodeling is essential for progressive course of juvenile idiopathic arthritis (JIA), therefore changes in glucosaminoglycans (GAGs) fractions with time in patients with JIA have been studied during 10-year follow-up. The study involved 22 healthy children (controls) and 83 patients with JIA aged from 2 to 18. The follow‑up study was yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(20 reference statements)
2
2
0
Order By: Relevance
“…Significantly lower urinary concentrations of sGAGs in JIA patients, especially in the afflicted girls, compared with healthy children, did not normalize with disease-modifying treatment with MTX, SSA, and EC, as well as with anti-cytokine treatment. The results obtained are consistent with the results of the research of other authors [4,19]. It should be pointed out, however, that Shevchenko et al [19] evaluated glycan levels by measuring daily urinary excretion of uronic acids in patients with different durations of JIA.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Significantly lower urinary concentrations of sGAGs in JIA patients, especially in the afflicted girls, compared with healthy children, did not normalize with disease-modifying treatment with MTX, SSA, and EC, as well as with anti-cytokine treatment. The results obtained are consistent with the results of the research of other authors [4,19]. It should be pointed out, however, that Shevchenko et al [19] evaluated glycan levels by measuring daily urinary excretion of uronic acids in patients with different durations of JIA.…”
Section: Discussionsupporting
confidence: 89%
“…The results obtained are consistent with the results of the research of other authors [4,19]. It should be pointed out, however, that Shevchenko et al [19] evaluated glycan levels by measuring daily urinary excretion of uronic acids in patients with different durations of JIA. The researchers observed lower urinary concentrations of the tested markers, especially in patients with a disease duration of 13 to 24 months.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, plasma levels of dermatan sulfates, hyaluronic acid, and keratan sulfates increased, while heparan sulfates did not change in these patients. Based on these studies, it can be concluded that different types of GAGs respond differently to factors leading to the manifestation of pathological changes of the osteoarticular system in children with JIA [ 5 , 23 , 24 , 25 , 26 ]. For instance, excessive release of DS chains and HA chains of lower molecular mass seem to contribute to JIA onset.…”
Section: Discussionmentioning
confidence: 99%